Analysis of the Money Supply and Interest Rate of Inflation in Indonesia - Darman Darman (The Winners, 2016)
Articleaimed to assess and analyze the effect of money supply and the interest rate on Inflation in Indonesia. This research applied descriptive quantitative approach with the nature of the explanatory method verification. The data used was secondary data in the money supply, interest rate and Inflation in Indonesia in 2000-2014. The results of this article are the partial test (t-test) indicates the money supply (X1), the rate of interest (X2) and there is no effect on Inflation (Y). While the results of the simultaneous test (F test) shows a strong and direct relationship between money supply and the interest rate on inflation. This means that the money supply and interest rates affect the rise and fall of inflation in Indonesia.